Biomolecular condensates in photosynthesis and metabolism. (December 2020) - Wunder, Tobias; Mueller-Cajar, Oliver
Abstract : The transient assembly or sequestration of enzymes into clusters permits the channeling of metabolites, but requires spatiotemporal control. Liquid liquid phase separation (LLPS) has recently emerged as a fundamental concept enabling formation of such assemblies into non-membrane bound organelles. The role of LLPS in the formation of condensates containing the CO2 -fixing enzyme Rubisco has recently become appreciated. Both prokaryotic carboxysomes and eukaryotic pyrenoids enhance the carboxylation reaction by enabling the saturation of the enzyme with CO2 gas. Biochemical reconstitution and structural biology are revealing the mechanistic basis of these photosynthetic condensates. At the same time other enzyme clusters, such as purinosomes for de-novo purine biosynthesis and G-bodies containing glycolytic enzymes, are emerging to behave like phase-separated systems. In the near future we anticipate details of many more such metabolic condensates to be revealed, deeply informing our ability to influence metabolic fluxes.